UPAYA GREEANPEACE MENJAGA KAWASAN PANTAI INDONESIA TERKAIT PROYEK PULAU REKLAMASI TELUK JAKARTA - Nonik Susanti; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The reclamation project in Jakarta Gulf that keeps on being controvertion in the middle of the society at this time doesn’t get yet the certain determination, whether it will be kept on, ot stopped, or there is advantageous solution for all people. Green peace Indonesia is one of international organization non-government that focuses on solving various problems of environment, reveals consistent to refuse the beach reclamation plan in Jakarta Gulf because the problem and ecology disaster will come and don’t respect the law norm and prevailed regulation.The method of data collecting is done by collecting secunder data, then analyzed in qualitative to obtain the draft about the main problem by using deductive method. The method of this research is the method of qualitative descriptive. The data is obtained through secunder data such as, book, journal, magazine, newspaper and website. From the result of research, that Greenpeace Indonesia observes all intelectual discussions, and the impact of ecology social that are already and will happen toward the society of the coastal area of Jakarta gulf. The government of Special Capital District of Jakarta needs to do the moratorium toward the blooming development of multistoried buildings, and more pay attention the sustainable means of livelihood for the people around Jakarta Gulf.Keywords: Greenpeace Indonesia, Reclamation, Jakarta Gulf